The role of foreign direct investment in a globalising economy - DUNNING, J.H. (PSL Quarterly Review, 2013)
The problem of mounting public debt should be attributed to the inability to control inflation instead of restricting public expenditures as many economists would suggest. The use of inappropriate monetary and fiscal tools to control inflation have aggravated the problem. In light of new findings, it is suggested that tax-based incomes policies and Lerner's market anti-inflation plan, among others, should be tried out. JEL Codes: